The Teaching of Pattern Comprehension in the 2nd Grade of Primary School Using Origami Applique - Grabauskienė, Vaiva; Lapėnienė, Rasa (Acta Paedagogica Vilnensia, 2019)
In this study, we investigated the expression of the pattern concept in primary education. For this purpose, we chose the concept of rhythm as a means of repeating found in different contexts. In Music and Arts, rhythm is first a way to make compositions. In the case of learning Math, rhythm can aid in comprehending various structures. We used action research in this article – our study contained some trials of learning to understand composition and structures by completing some origami applique tasks; pupils from the 2nd grade were our study participants. The study was held during the following 3 stages: the investigation of simple repeating, the exploration of rhythmical directional changes, and the examination of rhythmical size changes. Fourteen participants took part in the study. The pupils were asked to make some compositions of origami applique based on certain rules set for them. The participants had to also use their experience acquired in the aforementioned tasks for further tasks, which required them to create their own patterns. They had to realize the basic underlying structures for completing such tasks. The data were gathered by collecting paper crafts made by students and by audiotaping the discussions with these children. After employing content analysis, for the sake of visual illustrations of the results, the main features of various task performance were depicted using some typical real examples from the paper crafts of the students. The results showed that 2nd graders were able to replicate a simple rhythm without making mistakes. When creating line-type ornaments, they concentrated on one possible feature to make the rhythm, often mostly ignoring such possibilities as repetitions in number, direction, and size. After gaining some new knowledge during the process of origami applique activities designed to teach the possibilities in changing direction and size, the pupils were eager to apply various structures elsewhere. The children were fast to realize the importance of tidy composition, to solve the arising difficulties, and to generalize the experience in some other contexts.